2004
DOI: 10.1038/sj.npp.1300627
|View full text |Cite
|
Sign up to set email alerts
|

A Placebo Controlled Crossover Trial of Liquid Fluoxetine on Repetitive Behaviors in Childhood and Adolescent Autism

Abstract: Repetitive behaviors are a core symptom domain in autism that has been linked to alterations in the serotonin system. While the selective serotonin-receptive inhibitor fluvoxamine has been shown to be effective in adults with autism, as yet no published placebo controlled trials with these agents document safety and efficacy in children with autism. This study examines the selective serotonin reuptake inhibitor liquid fluoxetine in the treatment of repetitive behaviors in childhood and adolescent autism spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
217
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 344 publications
(221 citation statements)
references
References 26 publications
2
217
1
1
Order By: Relevance
“…In the author's opinion, the sub-threshold OC symptoms detected in our AS sample might be read as the sign of a phenomenological and possibly neurobiological overlap between ASD and OCD according to the concept of a broader spectrum of OC-related disorders, in line with previous bibliography [4]. This model seems sustained by some evidence derived from the association between ASD and OCD in family studies [1,14] and by some findings from clinical trials of a positive pharmacologic treatment response to SRIs in ASD [15,24,25].…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…In the author's opinion, the sub-threshold OC symptoms detected in our AS sample might be read as the sign of a phenomenological and possibly neurobiological overlap between ASD and OCD according to the concept of a broader spectrum of OC-related disorders, in line with previous bibliography [4]. This model seems sustained by some evidence derived from the association between ASD and OCD in family studies [1,14] and by some findings from clinical trials of a positive pharmacologic treatment response to SRIs in ASD [15,24,25].…”
Section: Resultssupporting
confidence: 82%
“…Higher prevalence of autistic traits has been found in OCD samples both in adults [5,6] and children [16], and some evidence suggests that treatments effective for OCD may be effective for repetitive thoughts and behaviours in ASD as well [15,19,24,25]. Also, family studies have reported an association between restrictive or repetitive behaviours in probands with autism and obsessive-compulsive features in parents both in multiplex [14] and sporadic autism families [1].…”
Section: Introductionmentioning
confidence: 99%
“…8,9 In addition, selective serotonin reuptake inhibitors (SSRIs) and atypical antipsychotic medications, which are often effective in autism to treat disruptive anxiety-related behaviors and aggression, respectively, act on the serotonin system. 10,11 Data thus suggest that at least some of the serotonin dysregulation in autism families is not secondary to autism, but rather may inform us about a heritable predisposing factor.…”
Section: Introductionmentioning
confidence: 99%
“…35 Three of these 5 published trials reported a statistically significant benefit of SRI treatment in ASD. [46][47]49 Two published trials and the 1 available unpublished trial reported some or no benefit of antidepressant treatment. 35,48,50 Efficacy of SRI Treatment of Autism Our literature search first alerted us to the presence of 5 completed studies that were possibly eligible for inclusion in this meta-analysis but remained unpublished at the time the manuscript was put together, thus suggesting the presence of publication bias in the field.…”
Section: Included Studiesmentioning
confidence: 99%
“…Table 1 presents the characteristics of the 5 published trials [46][47][48][49][50] and the 1 unpublished trial included in this meta-analysis. 35 Three of these 5 published trials reported a statistically significant benefit of SRI treatment in ASD.…”
Section: Included Studiesmentioning
confidence: 99%